PERANAN PEREMPUAN DALAM PEREKONOMIAN KELUARGA DENGAN MEMANFAATKAN SUMBERDAYA PERTANIAN - Bertham, Yudhy Harini; Ganefianti, Dwi Wahyuni; Andani, Apri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
This study aims to find out the reasons women decide to work as a farmer, knowing the understanding of women in the utilization of agricultural resources, and know how big the role of women in the intensification of the family economy. The method to determine the respondent used in this research is census method with numbering 100 persons. Analysis of the data used is descriptive analysis and qualitative analysis of revenue contribution. The results showed that the reasons women choose to work as farmers because of their desire to help their husbands in contributing family income which is driven by the load factors of family burden. Looking for experiences and shared responsibility are other reasons for women to work in agricultural activities. Their knowledge and understanding of agriculture, women are only know how to grow crops and produce. Stages how sustainable farming, care for the environment with organic farming systems is not yet implemented. This is caused by the lack of knowledge of owmen. Income contribution of women to family incomes is high, with a range of contribution 40% - 59% of total family income. This condition can be a reason for women to participate in decision-making within the household. So the presence of women within the family becomes more important and appreciated.